Enhancing Teachers’ Professional Competence in the Era of Society 5.0 - Murni, Siti; Sartika, Diana; Mardina, Dini (Ahlussunnah: Journal of Islamic Education, 2026)
The emergence of Society 5.0 highlights the integration of advanced technology with human-centered values, creating new challenges in education. Teachers are required to adapt to technological developments, strengthen digital literacy, and foster students’ critical and adaptive thinking. For Islamic Education teachers, these demands are more complex as they also carry responsibility for developing students’ moral and spiritual character. This study aims to examine the strategies of Islamic Education teachers in enhancing their professional competence in the era of Society 5.0, as well as to identify supporting and inhibiting factors. This research employs a qualitative method with a case study approach. Data were collected through interviews and documentation and analyzed using data reduction and data display techniques. The findings indicate that teachers understand Society 5.0 as the integration of technological advancement with humanistic and Islamic values. Efforts to enhance competence include the use of digital learning media, strengthening literacy and digital skills, improving instructional leadership, developing foreign language proficiency, and optimizing the use of information technology in both teaching and administrative processes. These efforts reflect the integration of cognitive, professional, social, and personal competencies required for effective teaching in contemporary educational contexts.